ISOLATION OF LACTIC ACID BACTERIA FROM TEMPOYAK AND ITS ANTIMICROBIAL ACTIVITY ON THE Escherichia coli - Eliya Mursyida; Fifi Candita; Muhammad Faisal; Deinike Wanita Marwan (Biology Department, Mathematics and natural science, Tadulako University, 2022)
Diarrhea is a potential extraordinary event that can cause death. The most common microbes that cause diarrhea in developing countries are Rotavirus and Escherichia coli. One of the treatment of diarrhea is by giving antibiotics. However, the use of antibiotics is known to disrupt the balance of normal gastrointestinal flora, thereby changing the composition of the microbiota. Probiotics can be given to balance the normal flora during or after treatment with antibiotics. Lactic acid bacteria (LAB) is one of the probiotics that can inhibit the growth of pathogenic microbes and is commonly found in fermented foods. This study aimed to isolate LAB from tempoyak made from kampar durian, Riau Province, Indonesia and test its antimicrobial activity against Escherichia coli. The study was initiated by isolating LAB from tempoyak using the multilevel dilution method, followed by characterizing LAB by colony and cell morphology, and testing its antimicrobial activity against Escherichia coli using the agar well diffusion method. The antimicrobial activity test results were analyzed using one-way ANOVA and Bonferroni follow-up test. The results of LAB characterization showed that four LAB isolates had different colony morphology, including spherical Gram-positive bacteria and catalase-negative bacteria. The results of the antimicrobial activity test showed that LAB1 isolates had the highest ability to inhibit Escherichia coli with an average inhibition zone diameter of 15.21 mm and the lowest inhibition zone was found in LAB 4 isolates, which was 10.80 mm. The results of the one way ANOVA test showed a significant difference between the four LAB isolates in inhibiting Escherichia coli with P value <0.05. In the Bonferroni test, there were significant differences between LAB 1 and LAB 4 isolates. It can be concluded that LAB isolated from tempoyak has the potential to be a source of probiotics.